CAPACIDADE FUNCIONAL NO IDOSO AVANÇADO: ESTUDO COMPARATIVO DE CARACTERÍSTICAS CLÍNICAS, HEMODINÂMICAS E ELETROCARDIOGRÁFICAS - Melhem Junior, Abrao Jose (2020)
Population aging is a reality and, among the demands of older age groups, health stands out, due to the action of aging in the body and the high prevalence of chronic diseases, with increasing financial expenditures. The advanced elderly group, over 75 years old, is projected to reach 8.2% or 19.4 million people in 2040, in Brazil. Strategies that promote active aging can enhance functionality of the elderly, one of which is the practice of physical activity, which can prevent debilitation and chronic diseases. Functional capacity assessment can collaborate in the promotion of physical activity. One of the accessible assessments of functionality is the maximum oxygen utilization capacity (VO2max), which can be obtained, among other ways, by the exercise test (ET) on a treadmill. The objective of this research is to compare clinical, hemodynamic and electrocardiographic characteristics of advanced older adults submitted a ET, and to identify differences between elderly people with low capacity to exercise (group A) and those with greater functional capacity (group B), through VO2max, using as cutoff point of 24 mg/kg/min. Retrospective research on reports and medical records was conducted on a series of cases (n = 86, 39 men, 47 women), of older adults over 75 years old, submitted to ET in Guarapuava, PR, Brazil. Comparisons were made based on VO2max (Group A <24ml / kg / min; Group B≥24ml / kg / min). Statistical analysis included Chi-square test for the categorical variables, Student's t test for the continuous variables, Spearman's Rô tests for correlations when applied, and the Hedges‘ g for measuring the sample size effect. In the overall analysis of the sample, high rates of sedentary lifestyle were observed (75.6%), with a predominance in cardiac patients (82.7%), especially in women with heart disease (93.1%). Dyslipidemia (63.8% x 41.0%, p = 0.035) and accumulated risk factors (RF) (3 or more x 3 or less, p = 0.001) predominated in women compared to men. Women also had a greater number of changes in the resting ECG (93.6% x 71.8%, p = 0.006). The incidence of arrhythmias increased from 23.3% at rest, to 76.7% on exertion and 66.3% on recovery (p = 0.001). When comparing functional capacity, Group A had more recommendations to the test due to symptoms (p = 0.034), higher body mass index (BMI) (p = 0.045), lower heart rate (HR) reserve (p = 0.043) and more exacerbated responses of systolic (RPAS) (p = 0.008) and diastolic (RPAD) (p = 0.047). Comparing the components of the HR reserve with the pressure responses, it was observed that the initial HR was higher in cases with exacerbated RPAS (p = 0.032) and exacerbated RPAD (p = 0.033). The initial HR was also directly correlated to the BMI (p = 0.01, Spearman‘s rho= 0,272). Other finding was that the recovery of HR in the first minute after the effort peak was more delayed in people with greater initial HR (90,9 x 81,2bpm, p=0,006, g=0,21) and lower FC reserve (42,5 x 57,0 bpm, p=0,001, g=0,25). In conclusion, recommendation for the test to check symptoms, body mass index, heart rate reserve and blood pressure responses showed differences when compared by functional capacity in this specific population, which is increasing in number, functionality, risk factors and chronic diseases.